Analisis Fundamental Dan Teknikal Saham PT. Bank Syariah Indonesia Tbk. (BRIS) - harits santoso (ITB AAS INDONESIA Surakarta, 2023)
This study aims to understand the company's performance of PT Bank Syariah Indonesia by approaching fundamental and technical analysis considering the company's performance in line with fluctuations in stock prices on the Indonesia Stock Exchange. The methodology of this study uses descriptive qualitative. The analytical techniques used in the study are fundamentant analysis and technical analysis at PT. Bank Syariah Indonesia Tbk. The data used in this study uses financial report data and statistical data on stock price movements from the Indonesia Stock Exchange. The findings from the study provide results of fundamental performance trends from 2016-2022 (quartal3) leading to positive performance in terms of EPS, ROE and ROA ratios. Meanwhile, in terms of technical analysis, it experienced a down trend phase starting from the IPO until March 2020 then reversed the trend direction to become an up trend phase until February 2021 and returned to the dowm trend phase until now (November 2022).